Art and Curriculum - Viramontes Cabrera, Sonia; Acosta Escareño, Javier (Historia y Comunicación Social, 2014)
Reflections, questions and answers to revolve around the feasibility of mindset complex in the Bachelor´s degree in Arts of University Autonomous of Zacatecas.